2022
DOI: 10.3390/cells11213417
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Studies of Hydrogenated Titanium Dioxide Nanotubes with Superhydrophilic Surfaces during Early Osseointegration

Abstract: Titanium-based implants are often utilized in oral implantology and craniofacial reconstructions. However, the biological inertness of machined titanium commonly results in unsatisfactory osseointegration. To improve the osseointegration properties, we modified the titanium implants with nanotubular/superhydrophilic surfaces through anodic oxidation and thermal hydrogenation and evaluated the effects of the machined surfaces (M), nanotubular surfaces (Nano), and hydrogenated nanotubes (H-Nano) on osteogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…This increase, in turn, could potentially support enhanced matrix mineralization. Similar effects were observed in previous studies, where higher roughness levels ensured better tissue adhesion and integration between the implant and bone, subsequently positively impacting the healing time after implantation [ 64 , 65 ]. Moreover, osteogenic differentiation is recognized as a multistep process characterized by a peak in ALP activity, followed by a subsequent decline during the mineralization phase [ 66 ].…”
Section: Discussionsupporting
confidence: 85%
“…This increase, in turn, could potentially support enhanced matrix mineralization. Similar effects were observed in previous studies, where higher roughness levels ensured better tissue adhesion and integration between the implant and bone, subsequently positively impacting the healing time after implantation [ 64 , 65 ]. Moreover, osteogenic differentiation is recognized as a multistep process characterized by a peak in ALP activity, followed by a subsequent decline during the mineralization phase [ 66 ].…”
Section: Discussionsupporting
confidence: 85%
“…Titanium (Ti) and its alloys were extensively employed as orthopedic implants due to their commendable properties, such as low density, favorable corrosion resistance, and mechanical characteristics. Nevertheless, due to its intrinsic biological inertness, Ti-based implants exhibit incapacity of resisting bacterial invasion and promoting osseointegration. Consequently, diverse surface modification approaches have been explored to enhance the bioactivities of Ti implants. Electrochemical anodization is a widely employed technique for Ti implants by creating a layer of titanium dioxide nanotubes (TNT) on its surface. , The textured architecture of TNT has demonstrated its capacity to promote the growth and differentiation of osteoblasts to a certain extent. , Moreover, TNT exhibits an inherent capability for the incorporation of functional elements (e.g., Sr, Na, Ag, and Ca) via hydrothermal treatment, resulting in the formation of titanate nanotubes and an enhancement in their function. Furthermore, the hollow tubular structure of titania/titanate nanotubes facilitates the loading of diverse drugs, including osteogenic and antibacterial agents, thereby conferring specific functionalities to Ti orthopedic implants. However, a challenge associated with antibacterial agent loading is the phenomenon of initial burst release, which is unnecessary in the absence of infection and may lead to adverse effects on the host. , Additionally, the uncontrolled release of antibacterial agents, such as antibiotics, inevitably results in the development of drug-resistant bacteria and makes treatment more difficult. …”
Section: Introductionmentioning
confidence: 99%
“…Understanding cellular behavior in contact with different surfaces is of fundamental interest to produce optimal multiscale topography, therefore modulate and accelerate the interface constitution, improving the bone integration of bone implants [19,20]. A recent work demonstrated that a nanotubular/superhydrophilic surface accelerated osteogenesis and osseointegration in a rabbit femur implant model [21]. These results were observed mostly at a late phase of healing.…”
Section: Introductionmentioning
confidence: 99%